Optimal dose and duration of iron supplementation for treating iron deficiency anaemia in children and adolescents: A systematic review and meta-analysis. - Tanveer Rehman; Ritik Agrawal; Farhad Ahamed; Saibal Das; Srijeeta Mitra; Dinesh Kumar; Chinmayee Sethy; Srikanta Kanungo; Debdutta Bhattacharya; Sanghamitra Pati (PLoS ONE)
Introduction Iron deficiency anaemia (IDA) accounts for nearly two-thirds of all anaemia cases globally. Despite the widespread use of iron supplementation, the optimal dose and duration for treating IDA remain unclear. In this study, we aimed to determine the most effective dose and duration of iron supplementation for improving haemoglobin (Hb) levels in children and adolescents (≤19 years) with IDA. Methods A systematic review and meta-analysis were conducted. We searched MEDLINE, Embase, CINAHL, and the Cochrane Library for peer-reviewed studies published between 2013 and 2024. The interventions included iron supplementation with a defined dose and duration of at least 30 days. Comparators were placebo, no treatment, or alternative regimens. The outcome was the change in Hb levels. Eligible studies included IDA cases diagnosed through ferritin level measurements in healthy individuals. Studies involving pregnant women or children with underlying conditions were excluded. A meta-analysis was performed using standardized mean differences to pool effect sizes for Hb improvement with 95% confidence intervals (CIs). Subgroup analyses were performed for different treatment durations (<3 months, 3-6 months, >6 months) and dosage categories (<5 mg/kg/day, 5-10 mg/kg/day, >10 mg/kg/day). A random-effects meta-regression model was used to determine the optimal dose and duration, accounting for known covariates affecting Hb improvement. Results A total of 28 studies with 8,829 participants from 16 countries were included. The pooled effect size for Hb improvement was 2.01 gm/dL (95% CI: 1.48-2.54, p < 0.001). Iron supplementation for less than 3 months showed the highest significant effect size (2.39 gm/dL, 95% CI: 0.72-4.07), followed by treatments exceeding 6 months (1.93 gm/dL, 95% CI: 0.09-3.77). The lowest effect size was observed in treatments lasting 3-6 months (1.58 gm/dL, 95% CI: 0.93-2.23). Low-dose iron supplementation (<5 mg/kg/day) demonstrated favourable trends in Hb improvement, particularly in individuals with lower baseline Hb levels. Oral ferrous sulphate had a significant effect (2.03 gm/dL, 95% CI: 1.24-2.82), while parenteral ferric Carboxymaltose showed consistent efficacy. Conclusion Low-dose iron supplementation (<5 mg/kg/day) combined with treatment durations of either less than 3 months or more than 6 months, is optimal for improving Hb levels in children and adolescents with IDA. Tailoring treatment based on baseline Hb levels and anaemia severity is essential. These findings provide evidence to support updated guidelines on iron supplementation in paediatric and adolescent populations and inform national anaemia management programmes. Trial registration Prospero registration number: This study was registered with PROSPERO (CRD42024541773).